The Art and Science of Civil Resistance - Chenoweth, Erica (Thammasat Review, 2015)
My introduction to civil resistance was accidental. In June 2006, I was a doctoral student at the University of Colorado-Boulder in the United States, where I was in the final stages of writing my dissertation in political science. The topic was a fairly typical one for a traditional security studies student like myself. I was curious about why terrorism occurs so often in democratic countries, and I had endeavored to develop a novel explanation for why this was the case and to test that explanation using quantitative analysis of large-scale observational data (my particular skill set at the time). Earlier that summer, I received an email invitation to an academic workshop called “People Power and Pedagogy,” which aspired to introduce social scientists to the literature on nonviolent or “civil” resistance—a method of conflict where unarmed civilians use a variety of methods like strikes, protests, boycotts, stay-aways to actively confront an opponent without using or threatening to use violence. I was totally unfamiliar with the concept of civil resistance. In my four years of graduate school, the emphasis had been on developing our skills of hypothesis-testing and inquiry and, in my particular subfield, understanding violence and its uses. Nonviolent action was entirely sidelined from this conversation. In all of my time researching social movements, political power, and organized violence, I had never been exposed to scholarship that explored the pragmatic techniques of Mahatma Gandhi, the leaders of the U.S. Civil Rights movement, or other similar cases. I had not once come across a single reference to Gene Sharp, the author of the seminal three-volume text The Politics of Nonviolent Action, nor any related research that had come afterward. (1) Needless to say, taking nonviolent resistance seriously as a subject of inquiry was a somewhat foreign concept.